Seasonal variation of Haematobia irritans in the Santa Catarina State plateau and eficiency of the "Directed Control" Variação sazonal de Haematobia irritans no planalto catarinense e eficiência do "Controle Dirigido". - de Souza A.P.* (2005)
This experiment had the aims of collecting information about seasonal variation; to evaluate the efficacy of the directed control method, in which only the most susceptible animals to Haematobia irritans infestations are treated and to reduce treatment costs. From February 2001 to April 2003, in two farms situated in Lages, Santa Catarina State, Brazil, two groups of 17 adult animals each (one group per farm) were used to count fly infestation every 14 days. In farm I, 29.4% of the animals were treated with pour-on cypermethrin, at 5 mg/kg live weight, when infestations reached an average above 200 flies (Directed Control). In farm II, treatments were used according to the farmer's decision. Evaluations of the efficacy of treatments were performed 1 to 7 days after treatment. The heaviest infestations occurred from November to April, and the number of flies did not surpassed 115.25 in average. Animals in farm I were treated only once, in December 2001, and a reduction of the infestation of H. irritans of 89.35% was showed. The 29.4% of most susceptible animals, in the time of heaviest infestations, sustained 65.97% of the total population of H. irritans. In farm II, animals were treated 9 times, and the efficacy of the treatments reached 98.25%. It was found that in this farm an excessive number of treatments have been used for the control of H. irritans.